2015
DOI: 10.1111/ppa.12393
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Cerevisin via Agrobacterium tumefaciens‐mediated transformation affects microsclerotia formation and virulence of Verticillium dahliae

Abstract: Agrobacterium tumefaciens-mediated transformation (ATMT) was used to obtain a large number of Verticillium dahliae (Vd991) T-DNA insertion mutants that were randomly integrated. Insertion mutants that produced significantly fewer microsclerotia were chosen for further analysis. Mutant T0065 was identified as having the Cerevisin gene interrupted by T-DNA, and it was named cerevisin. The cerevisin protein showed a high amino acid sequence similarity with the vacuolar protease B. The mutant strain cerevisin disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Consistent with these results, deletion of Proteinase B homologous genes in V. dahliae (Vd991) also resulted in a significant decrease in the production of conidia, significant reduction in growth rate, and a reduction in virulence, relative to the wild-type (He et al 2015). Targeted disruption of the cellular serine proteinase ALP2-encoding gene in Aspergillus fumigatus also resulted in a slightly decreased rate of vegetative growth and a more than 80 % reduction in sporulation in the alp2-negative mutants, which was correlated with an approximate 50 % reduction in the median diameter of conidiophore vesicles (Reichard et al 2000).…”
Section: Functional Analysis Of Peprtsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with these results, deletion of Proteinase B homologous genes in V. dahliae (Vd991) also resulted in a significant decrease in the production of conidia, significant reduction in growth rate, and a reduction in virulence, relative to the wild-type (He et al 2015). Targeted disruption of the cellular serine proteinase ALP2-encoding gene in Aspergillus fumigatus also resulted in a slightly decreased rate of vegetative growth and a more than 80 % reduction in sporulation in the alp2-negative mutants, which was correlated with an approximate 50 % reduction in the median diameter of conidiophore vesicles (Reichard et al 2000).…”
Section: Functional Analysis Of Peprtsupporting
confidence: 59%
“…dahliae and Aspergillus fumigatus also exhibited a reduction in the radial growth rate (He et al 2015, Reichard et al 2000. Growth studies also indicated that the colony morphology of the ΔPeprt null mutant was different from that of the WT and the ectopic mutant (Fig.…”
Section: Functional Analysis Of Peprtmentioning
confidence: 96%
“…Subtilisin-like serine proteases are reported to be involved in the sporulation of M. oryzae and C. parasitica [25,34], and impacted the sclerotial development of V. dahlia [21]. Our results indicated that Bcser1 is essential neither for sporulation nor sclerotial formation in B. cinerea.…”
Section: Discussionmentioning
confidence: 66%
“…Subtilisin-like serine proteases are also reported to play important roles in the virulence of many pathogenic fungi [20]. Orthologous of Bcser1 and Bcser2 are widely present in pathogenic fungi, and they also have been reported to play important roles in the virulence of pathogenic fungi [12,21,22,34,37]. For example, disruption of Spm1, an orthologous of Bcser2 in the rice blast fungus M. oryzae, resulted in a significant reduction in virulence on seedlings of rice and barley [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation